2016
DOI: 10.1002/chem.201602913
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Roles of Isocyanides in Palladium‐Catalyzed Imidoylative Couplings: A Mechanistic Study

Abstract: Kinetic, spectroscopic and computational studies examining a palladium-catalyzed imidoylative coupling highlight the dual role of isocyanides as both substrates and ligands for this class of transformations. The synthesis of secondary amides from aryl halides and water is presented as a case study. The kinetics of the oxidative addition of ArI with RNC-ligated Pd species have been studied and the resulting imidoyl complex [(ArC=NR)Pd(CNR) I] (Ar=4-F-C H , R=tBu) has been isolated and characterized by X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 109 publications
1
12
0
Order By: Relevance
“…Metal-catalyzed isocyanide insertion reactions have attracted much recent attention, and a variety of heterocycles are now readily accessible by careful engineering of the substrate structure. As part of our research program aimed at exploiting the diverse reactivities of the isocyano group, we recently reported metal triflate-catalyzed domino processes initiated by the insertion of isocyanide into the N–H bond of amines . We document herein the synthesis of 3,5,5-trisubstituted imidazolones 1 and quinazolin-4-ones 2 by silver nitrate-catalyzed reactions of primary amines with methyl α-isocyanoacetates and 2-isocyanobenzoates, respectively (eq 2, Scheme ).…”
supporting
confidence: 68%
“…Metal-catalyzed isocyanide insertion reactions have attracted much recent attention, and a variety of heterocycles are now readily accessible by careful engineering of the substrate structure. As part of our research program aimed at exploiting the diverse reactivities of the isocyano group, we recently reported metal triflate-catalyzed domino processes initiated by the insertion of isocyanide into the N–H bond of amines . We document herein the synthesis of 3,5,5-trisubstituted imidazolones 1 and quinazolin-4-ones 2 by silver nitrate-catalyzed reactions of primary amines with methyl α-isocyanoacetates and 2-isocyanobenzoates, respectively (eq 2, Scheme ).…”
supporting
confidence: 68%
“…Metal-catalyzed domino processes initiated by isocyanide insertion reaction has recently been developed into a powerful tool for the rapid construction of heterocycles. In connection with our research program aimed at exploiting the diverse reactivities of the isocyano group, we reported a silver nitrate-catalyzed synthesis of the 3,5,5-trisubstituted imidazolones 1 from methyl α-isocyanoacetates 3 and primary amines 4 . As a continuation of this research topic, we describe herein a three-component synthesis of 2,3,5,5-tetrasubstituted imidazolones 2 by a Pd/Cu-catalyzed reaction of methyl α,α-disubstituted α-isocyanoacetates 3 with primary amines 4 and aryl­(vinyl) halides 5 (Scheme c).…”
mentioning
confidence: 97%
“…Recent studies in the field of isocyanide insertions are directed towards further development of these imidoylative Buchwald-Hartwig type cross-couplings. To facilitate this, over the past couple of years there have been multiple reports on the mechanistic aspects of these reactions, allowing chemists to easier predict catalytic behavior and develop more effective catalysts [40][41][42].…”
Section: Cross-couplings With Oxygen or Nitrogen Nucleophilesmentioning
confidence: 99%